Congenital atresia of the submandibular gland duct: report of two clinical cases with spontaneous regression and literature review - Oliveira Freitas, Lara; Seixas Mourão, Priscila; Gonçalves, Moisés Willian Aparecido; Ramos-Jorge, Maria Letícia; Marques Mesquita, Ana Terezinha (Revista Estomatología, 2022)
Background: Congenital atresia of the submandibular gland duct is a rare condition, originated during the embryogenic process, characterized by swelling in the region of the oral floor. A few cases of congenital atresia of the submandibular gland duct have appeared in the literature and only one reports no surgical intervention to date. Case series: In the present study reports two cases of babies with clinical findings demonstrating swelling well-defined in the region of the oral floor, slightly translucent bluish color, painless to palpation, without finding stones or salivary drainage and apparently with no perforation of the submandibular gland duct. Both patients were kept under observation, later presenting spontaneous regression. Conclusion: This study highlights the importance of conducting a thorough clinical examination in addition to showing that the use of complementary exams may not be essential.